2013
DOI: 10.1186/1471-2458-13-1060
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries in 14- and 15-year-olds in New South Wales, Australia

Abstract: BackgroundDental caries remains one of the most common chronic diseases of adolescents. In Australia there have been few epidemiological studies of the caries experience of adolescents with most surveys focusing on children. The New South Wales (NSW) Teen Dental Survey 2010 is the second major survey undertaken by the Centre for Oral Health Strategy. The survey is part of a more systematic and efficient approach to support State and Local Health District dental service planning and will also be used for Nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 8 publications
0
21
1
Order By: Relevance
“…Within each school, a simple random sample of individuals of the involved age group was selected, and the response rate was 40.08%. In this sense, studies with higher (19), similar (8,20) and lower response rates compared with the present study are found in the literature (21). The response rate in the present study may represent its own limitation.…”
Section: Discussioncontrasting
confidence: 48%
“…Within each school, a simple random sample of individuals of the involved age group was selected, and the response rate was 40.08%. In this sense, studies with higher (19), similar (8,20) and lower response rates compared with the present study are found in the literature (21). The response rate in the present study may represent its own limitation.…”
Section: Discussioncontrasting
confidence: 48%
“…Consequently, the state of oral health in adolescents over 15 years old and young adults under 25 years old represents a large gap in knowledge at the national and international level (9).…”
Section: Introductionmentioning
confidence: 99%
“…14 In Australia, the mean DMFT values for 14-and 15-year-olds have remained fairly stable over the last decade. 15 The SiC index below 5 was suggested by Marthaler et al to be the global goal for the 15-year-olds. 13 In Switzerland, the SiC index value dropped from 4.91 in 1996 to 4.31 in 2000.…”
Section: Discussionmentioning
confidence: 99%